Pesticide management knowledge, attitude and practices in Indonesian vegetable farmers with Occupational Skin Disease in Magelang, Central Java: Pesticide-related Skin Disease and KAP in Farmers - Febriana, Sri Awalia; Khalidah, Miya; Huda, Fariz Nurul; Sutarni, Sri; Indrastuti, Niken; Setyopranoto, Ismail; Waskito, Fajar; Mauleka, Rusdy Ghazali (Journal of Pakistan Association of Dermatologists, 2022)
Background: Agriculture is a significant sector in Indonesia with almost 35.76 million labors involved and pesticides are widely used to increase yields. However, pesticide exposure due to improper application, inappropriate storage practices and substandard use of protective equipment may produce a number of occupational skin problems. This study aims to assess the knowledge, attitude, and practices (KAP) of pesticide management and the prevalence of occupational skin diseases related to pesticide exposure in Ngablak, Magelang. Methods: We conducted a cross-sectional study involving 105 vegetables farmers from 3 hamlets. Data were collected through workplace observation, guided interviews by questionnaires, and dermatology examination. Results: Most of the farmers (89.5%) sprayed pesticide in the morning and 89.5% of farmers spent less than five hours of spraying. The majority of farmers (64.8%) mentioned not to spray pesticides against wind directions. The percentage of respondents who comprehend the information listed in pesticide labels is low (22.8%). The prevalence of skin disease related to the pesticide was 42.9% of the farmers with 11.4% having pesticide contact dermatitis. The moderate farmers are aware of dosage and direction of use, but they do not acknowledge emergency information, approval number, the date of manufacture, and expiry date as listed in pesticide labels. Conclusions: The KAP of pesticide management among vegetable farmers is low with a high prevalence of occupational skin disease related to pesticide exposure in Ngablak, Magelang. Keywords: occupational skin disease, pesticide, KAP, personal protective equipment, vegetable farmers